Factors Associated With Coverage of Health Insurance Among Women in Malawi - Chauluka, Margaret; Uzochukwu, Benjamin S. C.; Chinkhumba, Jobiba (Frontiers in Health Services, 2022)
Introduction Access to healthcare for the vulnerable groups including women has long been a theme encouraged worldwide from the first general assembly on health to the current sustainable development goals. Despite many countries having a free public healthcare system, there are inequalities in access to care and significant out-of-pocket spending, pushing most women into poverty against the principles of universal health coverage. Coverage of Malawian women with health insurance is poor; thus, there is limited cushioning and high risk of poverty, as women bear costs of care as primary caregivers. There is need to explore determinants of coverage of health insurance among women in Malawi to inform health policy. Methodology This study was quantitative in nature, using cross-sectional secondary data from the 2015 to 2016 Malawi Demographic and Health Survey involving women aged between 15 and 49 years. We assessed factors associated with insurance coverage by comparing women with and without insurance schemes using binary logistic regression. Analysis was done using STATA statistical package version 13. Results The analysis included a total of 24,562 women with a mean age of 28 SD (9.3). Of these cases, 1.5% had health insurance. High education attainment, occupation, and wealth were significantly associated with health insurance ownership, with all having p-values of < 0.01. On the other hand, a woman's residence, marital status, and who heads a household were not associated with ownership of health insurance significantly. Conclusion Education, occupation, and wealth have a key role in influencing a woman's choice in owning health insurance. This informs policymakers and health insurance providers on how best to approach women's health financing and factors to target in social security programs and health insurance products that speak to women's needs and capacity.